2019
DOI: 10.1186/s12872-019-1061-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival and quality of life in Jehovah’s witnesses after cardiac surgery: a case control study

Abstract: Background We previously analyzed morbidity and mortality in Jehovah’s Witnesses patients after cardiac surgery compared to control population patients. Patients who were Jehovah’s Witnesses were operated in accordance with their philosophical convictions and in respect of their refusal of transfusions. We propose to assess long-term survival and quality of life in the patients of this preliminary study. Methods We contacted 31 adult Jehovah’s Witnesses patients who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Our current study compared 32 consecutive Jehovah's Witnesses undergoing cardiac surgery with a matched cohort of non-Witnesses. Although the sample size appears relatively small, it is consistent with similar group sizes in other published studies [9,13,[15][16][17]. The small cohort was characterized by a nearly balanced gender ratio and below-average weight and BMI.…”
Section: Discussionsupporting
confidence: 87%
“…Our current study compared 32 consecutive Jehovah's Witnesses undergoing cardiac surgery with a matched cohort of non-Witnesses. Although the sample size appears relatively small, it is consistent with similar group sizes in other published studies [9,13,[15][16][17]. The small cohort was characterized by a nearly balanced gender ratio and below-average weight and BMI.…”
Section: Discussionsupporting
confidence: 87%
“…More details on exclusion reason are available from Table S9, Data S1. This left 41 studies published in 42 reports meeting the criteria for inclusion in our review 14–55 …”
Section: Resultsmentioning
confidence: 99%
“…The authors employed the MacNew questionnaire, which showed no difference in physical (p = 0.54), emotional (p = 0.12), social (p = 0.21) and global (p = 0.25) scores between the two populations. 63…”
Section: Morbiditymentioning
confidence: 99%
“…Future research is needed to provide greater clarity on the outcomes of cardiac surgery in Witnesses that refuse blood products. There needs to be an increased focus on multi-institutional studies with a greater number of participants to validate the research to date, 8,63 along with readmission rates and long term mortality following discharge, 2 and a more in depth cost analysis of pre-, intra-, and post-operative optimisation of witnesses during cardiac surgery. 8…”
Section: Limitations and Future Researchmentioning
confidence: 99%